Suggested Corrections to Textbook Entitled: “Mudah Melakukan Percakapan Bahasa Mandarin Sehari-Hari” - Sudono Noto Pradono (Magister Scientiae, 2012)
The purpose of this paper is to criticize a published book. The writer reviewed a book entitled “Mudah melakukan percakapan Bahasa Mandarin sehari-hari” (“It is easy to speak everyday Chinese”). The writer found many mistakes in this book, which he classified as follows: 1. phonetic, 2. character, 3. diction, and 4. grammar; he focused on the sentences in the conversation part only. Therefore, the mistakes are discussed and the corrections are suggested. The writer hopes that there are no mistakes anymore in published books for learning Chinese in Indonesia.